Leadership and the voluntary provision of public goods: Field evidence from Bolivia - Jack, B. Kelsey; Recalde, Maria P. (Elsevier, 2015)
We conduct a controlled field experiment in 52 communities in rural Bolivia to investigate the effect that local authorities have on voluntary public good provision. In our study, community members pool resources to provide environmental education material for local schools. We find that voluntary contributions increase when democratically elected local authorities lead by example. The results are driven by two factors: (1) authorities, like other individuals, give more when they are called upon to lead than when they give in private, and (2) high leader contributions increase the likelihood that others follow. Both effects are stronger when authorities, as compared to randomly selected community members, lead by example. We explore two underlying sources of leadership influence. First, we provide evidence that the effect of a leader's contribution is not limited to signaling the value of the public good. Second, we examine how leader characteristics affect the likelihood that others follow. Specifically, our study shows that authority influence is driven by a combination of formal leadership status, observable characteristics, and the amount that authorities contribute when they give publicly before others.